Factors Mediating Environmental Biofilm Formation by Legionella pneumophila - Abu Khweek, Arwa; Amer, Amal O. (Frontiers in Cellular and Infection Microbiology, 2018)
Abstract Legionella pneumophila (L. pneumophila) is an opportunistic waterborne pathogen and the causative agent for Legionnaires’ disease, which is transmitted to humans via inhalation of contaminated water droplets. The bacterium is able to colonize a variety of man-made water systems such as cooling towers, spas and dental lines and is widely distributed in multiple niches, including several species of protozoa and nematodes such as Caenorhabditis elegans (C. elegans). In addition to survival in planktonic phase, L. pneumophila is able to survive and persist within multi-species biofilms that cover surfaces within water systems. Biofilm formation by L. pneumophila is advantageous for the pathogen as it leads to persistence, spread, resistance to treatments and an increase in virulence of this bacterium. Furthermore, Legionellosis outbreaks have been associated with the presence of L. pneumophila in biofilms, even after the extensive chemical and physical treatments. In the microbial consortium-containing L. pneumophila among other organisms, several factors either positively or negatively regulate the presence and persistence of L. pneumophila in this bacterial community. Biofilm-forming L. pneumophila is of a major importance to public health and have impact on the medical and industrial sectors. Indeed, prevention and removal protocols of L. pneumophila as well as diagnosis and hospitalization of patients infected with this bacteria cost governments billions of dollars. Therefore, understanding the biological and environmental factors that contribute to persistence and physiological adaptation in biofilms can be detrimental to eradicate and prevent the transmission of L. pneumophila. In this review, we focus on various factors that contribute to persistence of L. pneumophila within the biofilm consortium, the advantages that the bacteria gain from surviving in biofilms, genes and gene regulation during biofilm formation and finally challenges related to biofilm resistance to biocides and anti-Legionella treatments.